Revisiting helicity parton distributions at a future electron-ion collider - Borsa Sanjuán, Ignacio (2020)
We studied the impact of future electron ion collider inclusive and semi-inclusive polarized deep inelastic scattering data will have on the determination of the helicity parton distributions. Supplementing the Monte Carlo sampling variant of the DSSV14 analysis with pseudodata on polarized inclusive and semi-inclusive electron-proton deep inelastic scattering with updated uncertainty estimates and for two different center-of-mass-system energies, s=44.7 GeV and s=141.4 GeV, respectively, and on inclusive electron-helium collisions at s=115.2 GeV, we find a remarkable improvement in the determination of the helicity distributions, especially at low parton momentum fraction x. While inclusive electron-proton data at the lowest energy configuration constrain significantly the gluon polarization down to x∼10-4, the higher energy configuration strengthens the constraint and extends it one decade further. On the other hand, semi-inclusive data achieves the hitherto elusive flavor separation for sea quarks that cannot be obtained from any other inclusive electromagnetic measurement. Collisions with helium complement inclusive proton measurements, pushing the constraints on the combined quark plus antiquark u, d and s polarizations to an unprecedented level.